Antagonism of Bcl-XL is necessary for synergy between carboplatin and BH3 mimetics in ovarian cancer cells. Issue 1 (December 2016) - Abed, Mohammed; Abdullah, Marwan; Richardson, Alan
Abstract Background BH3 mimetics are a class of drugs that antagonize the Bcl-2 family of apoptosis inhibitors. We have previously shown that these compounds can potentiate the activity of carboplatin against several ovarian cancer cell lines. However, recent clinical studies have highlighted that BH3 mimetics which antagonise Bcl-XL are associated with significant thrombocytopenia. This has led to the development of ABT-199 which specifically inhibits Bcl-2. Unfortunately, Bcl-XL appears to be more frequently deregulated in ovarian cancer than Bcl-2. We therefore compared the ability of ABT-199, and the Bcl-XL selective compound WEHI-539, to potentiate the activity of carboplatin in ovarian cancer cell lines. Methods WEHI-539, ABT-737 and ABT-199 were tested in combination with carboplatin using a panel of 6 ovarian cancer cell lines. The activity of the drugs was evaluated using cell growth assays, staining with trypan bue and measurement of apoptosis by measuring caspase 3/7 activity, PARP cleavage and annexin-V/propidium iodide staining. Results We found that WEHI-539 and ABT-737, but not ABT-199, were synergistic with carboplatin in cell growth assays and potentiated cell death when assessed by trypan blue staining. Furthermore, WEHI-539 and ABT-737 augmented carboplatin induced caspase 3/7 activity, PARP cleavage and annexin V labelling, but ABT-199 failed to do so. Conclusions These observations suggest that compounds which target Bcl-XL are necessary if BH3 mimetics are to be successfully used to treat patients with ovarian cancer and this highlights the need to develop strategies to minimize thrombocytopenia induced by such compounds.